Tra realtà e singolarità: la teoria del soggetto nel pensiero di Fichte - Rametta, Gaetano (Revista Eletrônica Estudos Hegelianos, 2017)
ABSTRACT: This paper aims to analyze the concepts of subject and singularity in Fichte’s philosophy, since the early phase of his thought until the last phase, which developed in Berlin. More specifically, we intend to shed light on some fundamental issues of Fichte’s philosophical proposal, such as the scientific foundation of the system on a principle and its relation to the subject. The paper shows that Fichte diverges from Hegel in a way that is irreconcilable especially with regards to the concepts of contradiction and becoming.